Intervensi Kemanusiaan Dewan Keamanan Perserikatan Bangsa-Bangsa Terhadap Tindakan Pelanggaran Hak Asasi Manusia Di Myanmar - Halfiandara Alfazr Afifudin; Josina Augustina Yvonne Wattimena; Irma Halimah Hanafi (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Human rights violations committed by the Burmese Buddhist junta government, supported by the Myanmar government and even the military junta formed an anti-Islam movement among the Rakhine Buddhist community and the population of Myanmar.Purposes of the Research: This study aims to find out and understand about the United Nations Security Council's Humanitarian Intervention Against Human Rights Violations in Myanmar that can be justified according to international law. The Legal Impact of the UN Security Council's Humanitarian Intervention on the Actions of Criminals in Myanmar. Methods of the Research: The research method in this study is a normative legal research, using a law approach and a conceptual approach. Sources of research data include primary, secondary, tertiary legal sources. Data collection techniques in the form of literature study. Processing and analysis of legal materials used in writing is using qualitative analysis method.Results of the Research: The result obtained is that the UN Security Council's humanitarian intervention against acts of human rights violations in Myanmar can be justified in accordance with international law, because the UN Security Council's intervention is expected to resolve the problems in Myanmar, namely the conflict between the Rohingya (Muslim) and Rakhine (Buddhist) ethnicities which caused Rohingya ethnic groups have received unfair treatment from the Myanmar administration and military junta who have committed acts of human rights violations against the Rohingya, such as refusing to grant citizenship status, expulsion, torture, killing, and illegal detention.